Cannabinoids in the Treatment of Cannabis Use Disorder: Systematic Review of Randomized Controlled Trials - Vuilleumier, Caroline; Scherbaum, Norbert; Bonnet, Udo; Roser, Patrik (Frontiers in Psychiatry, 2022)
Background: The prevalence of cannabis use and cannabis use disorders (CUD) has significantly increased over time. However, there are no approved pharmacological treatments for CUD. The aim of this study was to determine the efficacy and safety of various medical cannabinoids in the treatment of CUD. Methods: We conducted a systematic review of randomized controlled trials which evaluated the therapeutic potential of medical cannabinoids in individuals with CUD and summarized the main study outcomes in terms of cannabis use, abstinence, withdrawal symptoms, craving, retention in treatment and adverse events. Results: We identified eight trials with a total of 667 study participants. Dronabinol reduced cannabis withdrawal symptoms whereas nabiximols, cannabidiol and PF-04457845, a fatty acid amide inhibitor, also reduced cannabis use and improved abstinence, compared to placebo. Nabilone failed to demonstrate efficacy in the treatment of CUD. All medications were well-tolerated. Conclusions: Cannabinoid receptor agonists, i.e., dronabinol and nabilone, showed only limited or no therapeutic potential in the treatment of CUD. In contrast, modulators of endocannabinoid activity, i.e., nabiximols, cannabidiol and PF-04457845, demonstrated broader efficacy which covered almost all aspects of CUD. Endocannabinoid modulation appears to be a promising treatment approach in CUD, but the evidence to support this strategy is still small and future research in this direction is needed.